2022
DOI: 10.18280/ts.390328
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Identification and Classification Algorithm for Plant Leaf Diseases Based on Deep Learning

Abstract: Identification of plant disease sis a difficult task for farmers. If the diseases are misidentified, there will be a huge crop failure, which threatens the living of farmers. This paper proposes a new tool for farmers to identify plant leaf diseases automatically, and provide solutions to this problem on expert database. Firstly, the infected spots of the leaf are recognized through fuzzy c-means clustering (FCM). Then, the features are extracted by gray-level co-occurrence matrix (COLCM), and classified by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To improve the result of the segmentation, researchers will Accuracy 91%. [56] FCM is used to find the spots on the leaf that are affected.…”
Section: Segmentation Process On Plant Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the result of the segmentation, researchers will Accuracy 91%. [56] FCM is used to find the spots on the leaf that are affected.…”
Section: Segmentation Process On Plant Leavesmentioning
confidence: 99%
“…The Hybrid dataset was 99.5% accurate, while the Fruit dataset was 94% accurate, and the Leaf dataset was 97.7% accurate. This study shows that 97% of the time, sick leaf spots are found using fuzzy c-means grouping [56]. Grey-level co-occurrence matrix (COLCM) is used to find the features, and progressive neural architecture search is used to put them into groups.…”
Section: Machine Learning Based Classifier Techniquesmentioning
confidence: 99%
“…All the nonlinear curve fits' correlation coefficients (R2) are more than 0.98. A novel tool for farmers to automatically detect plant leaf diseases is discussed in the study of [31]. The diseased leaf spots are first identified using fuzzy c-means clustering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sabrol and Satish [7] have used a classification tree for the purpose of tomato plant disease classification based on five types of tomato disease. A review on different ML classifiers such as SVM, KNN, RF, Naive Bayes (NB), Fuzzy classifier and artificial neural network is done in the plant disease research [8][9][10][11][12][13][14]. Bauer et al [15] have used high-resolution multi-spectral images for the classification of diseases in sugar beet leaves based on conditional random fields.…”
Section: Related Workmentioning
confidence: 99%